From Keys to Databases—Real-World Applications of Secure Multi-Party Computation. (12th September 2018) - Archer, David W; Bogdanov, Dan; Lindell, Yehuda; Kamm, Liina; Nielsen, Kurt; Pagter, Jakob Illeborg; Smart, Nigel P; Wright, Rebecca N
Abstract: We discuss the widely increasing range of applications of a cryptographic technique called multi-party computation. For many decades, this was perceived to be of purely theoretical interest, but now it has started to find application in a number of use cases. We highlight in this paper a number of these, ranging from securing small high-value items such as cryptographic keys, through to securing an entire database.